Membangun Kesadaran Anti-Korupsi: Sinergi Penegakan Hukum, Digitalisasi, dan Pendidikan Karakter Generasi Muda - Halimi, Baariq Hisyam (Maliki Interdisciplinary Journal, 2026)
Corruption in Indonesia remains a structural problem, with the 2025 Corruption Perception Index (CPI) score dropping to 34. This article analyzes anti-corruption efforts through three pillars: law enforcement, governance digitalization, and anti-corruption character education. Based on a literature review, the findings show that the 2025-2026 National Strategy for Corruption Prevention (Stranas PK) prioritizes digitalization through a GovTech super app, projected to save up to IDR 100 trillion, yet faces obstacles in infrastructure, human resources, and cybersecurity. Pancasila and religion based anti corruption education proves effective, while restorative justice and asset forfeiture (non conviction based) approaches need implementation. Success also depends on the role of youth, civil society, and cross institutional collaboration (KPK, Polri, Bappenas, Kemendagri). In conclusion, combating corruption requires a holistic, integrated approach to achieve the Golden Indonesia 2045 vision.